2009
DOI: 10.1063/1.3212695
|View full text |Cite
|
Sign up to set email alerts
|

Selective subsurface absorption of hydrogen in palladium using laser distillation

Abstract: A theoretical model for the selective subsurface absorption of atomic hydrogen in a Pd(111) surface by infrared (IR) laser pulses is presented. The dynamics of the adsorbate is studied within the reduced density matrix approach. Energy and phase relaxation of the hydrogen atom are treated using the semigroup formalism. The vibrational excitation leading to subsurface absorption is performed using rationally designed pulses as well as IR laser pulses optimized on-the-fly. It is shown that dissipation can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 73 publications
2
33
0
Order By: Relevance
“…These sets arise from the tunneling splitting of degenerate vibrationally excited levels and remaining degeneracies are indicated by the numbers in parentheses. In refs [17] and [18], only one value is reported per transition. The present results for vibrational wavenumbers are comparable to the previously reported values.…”
Section: Primary Results From These Experiments Is the Intermediate Scmentioning
confidence: 99%
See 1 more Smart Citation
“…These sets arise from the tunneling splitting of degenerate vibrationally excited levels and remaining degeneracies are indicated by the numbers in parentheses. In refs [17] and [18], only one value is reported per transition. The present results for vibrational wavenumbers are comparable to the previously reported values.…”
Section: Primary Results From These Experiments Is the Intermediate Scmentioning
confidence: 99%
“…Note that the kinetic energy operator contains non-diagaonal terms, when such coordinates are used [17]. For this three dimensional study, the analytical PES from [6] was first modified such as to describe a single hydrogen atom adsorbed on the palladium substrate.…”
Section: Primary Results From These Experiments Is the Intermediate Scmentioning
confidence: 99%
“…The dipole moment function was obtained from cluster model calculations using density functional theory. 23 In the case studied here, the dynamics follows the direction perpendicular to the surface. Furthermore, the component of ͑p͒ parallel to the surface is small in comparison to the perpendicular one.…”
Section: B Dynamical Simulationsmentioning
confidence: 97%
“…In addition, comparisons between six-dimensional quantum and classical calculations showed that the role of quantum effects in the hydrogen adsorption dynamics on surfaces is limited. [51,50] A coupling to phonons and electron-hole pairs has been considered in quantum mechanical studies addressing the subsurface adsorption of hydrogen, [16,52,53] but these calculations were performed in a lowdimensional framework.…”
Section: Introductionmentioning
confidence: 99%